Pedagogies for leading practice - Cheeseman, Sandra; Walker, Rosie (College teacher) (New York, NY : Routledge, 2019)
'Bringing together the experiences of professionals from around the world, this essential text explores the intersections between pedagogy and leadership to consider how effective Pedagogical Leadership can be used to foster the collaborative engagement of children and their families, staff and practitioners, and ensure high quality provision in early years settings and services. Pedagogies for Leading Practice showcases a vast range of experiences and ideas which are at the heart of professional practice. Written to provoke group discussion and extend thinking, opportunities for international comparison, points for reflection, and editorial provocations will help students, policy-makers and others engage critically with wide-ranging approaches to leadership in early years practice. Considering varied forms of collaborative working, the challenges involved in becoming a pedagogical leader, and the role of management in meeting insitutional demands and the needs of the wider community, chapters are divided into four key sections which reflect major influences on practice and pedagogy: - Being alongside children - Those who educate - Embedding families and communities - Working with systems Offering insight, examples and challenges, this text will enhance understanding, support self-directed learning, and provoke and transform thinking at both graduate and postgraduate levels, particularly in the field of early childhood education and care'--
Preface : finding purpose and direction / Michael Reed and Alma Fleet -- Engaging with data to foster children's learning : from population data to local projects / Sandra Cheeseman -- Leading pedagogical practice: co-constructing knowledge between educators and children / Rebecca Dalgleish -- Leadership for all - learning for all : making this visible by writing learning stories that enable children, families and teachers to have a voice / Lorraine Sands and Wendy Lee -- Editorial provocations : engaging readers and extending thinking / Rosie Walker -- Pedagogical leadership : interrogating self in order to lead others / Anthony Semann -- Pedagogical leadership : challenges and opportunities / Gaynor Corrick and Michael Reed -- Pedagogical leadership as ethical collaborative behavior / Andrew J. Stremmel -- Editorial provocations : engaging readers and extending thinking / Sandra Cheeseman -- Walking with families in an indigenous early childhood community / Jacqui Tapau and Alma Fleet -- Transformative pedagogical encounters: leading and learning in/as a collective movement / B. Denise Hodgins and Kathleen Kummen -- Utilising strengths in families and communities to support children's learning and wellbeing / Alison Prowle and Jackie Musgrave -- Editorial provocations: engaging readers and extending thinking / Rosie Walker -- Enacting pedagogical leadership within small teams in early childhood settings in Finland : reflections on system-wide considerations / Manjula Waniganayake, Johanna Heikka and Leena Halttunen -- Pedagogical leadership and conflict of motives in commercial ECCE environments / Sirene May-Yin Lim & Lasse Lipponen -- Pedagogic leadership within complex and changing ECEC systems / Christine Pascal and Tony Bertram with Delia Goodman, Ali Irvine and Judith Parr -- Editorial provocations : engaging readers and extending thinking / Sandra Cheeseman -- Coda : thinking forward / Alma Fleet and Michael Reed.
Includes bibliographical references.
Keywords: Educational leadership; Early childhood education